Dr Namrata TRUE TALES OF TEN T-PLL OVER A DECADE - Rajakumar, Dr Namrata.N.; Vijaya, Dr Raghavendra .H.; Horatti, Dr laxmi B; Balikai, Dr Girish; Shamnur, Dr Murugesh (International Journal of Medical Research and Review, 2023)
Background T- prolymphocytic leukemia(T-PLL) ,are aggressive lymphoid malignancies with unique morphologic, cytogenetic, immunophenotypic, and molecular features. T-PLL is a mature T-cell leukemia typically presenting at stages of exponentially rising lymphocyte counts in peripheral blood,accompanied by splenomegaly and bone marrow involvement. They are extremely rare ,comprising of <2% of mature T –leukemias and inherently aggressive and notoriously refractory to therapeutics.Extensive search for Indian literature on T-PLL and Immunophenotypic characterization of this entity did not yield any results. We analysed the characteristics, prognostic factors, outcomes and treatments of 10 patients with T-PLL . To our knowledge this is the largest series of T-PLL from India , this study reviews clinical, cytogentic and flow cytometric immunophenotyping findings, and differential diagnosis of patients with T-cell prolymphocytic leukemia from January 2012 to January 2022.Methods: Our laboratory received 4500 clinically suspected chronic leukemias, during a period of 10 years ,at kidwai memorial institute of oncology ,which is state cancer institute , where diagnostic flow cytometric analysis was done and leukemias were classified based on WHO 2008 criterias. Results: out of 4500 cases of Chronic lympho proliferative disorders sent for flow cytometric immunophenotyping, only 10 cases were diagnosed as T-PLL .Study period January 2012 to January 2022.Conclusions: Evaluation of immunophenotype of this rare entity by flow cytometry is a critical part of diagnosis and is a indespensible tool in distinguishing T-PLL from other mature T-cell lymphoid neoplasms.Awareness of this rare entity aids in work up .